Capital Structure Dynamics and Bank Affiliation of Business Groups: Evidence from Pakistan - Qamar Uz Zaman Malik (SEISENSE (PRIVATE) LIMITED, 2018)
Objective – An empirical investigation to assess the impact of the bank-affiliated business group on firm’s capital structure decisions. Design/methodology/approach – A sample of 146 group affiliated firms and subsamples for bank and non-bank affiliated firms was analyzed with random-effect panel regression model to determine the relationship of the bank-affiliated business group on firm’s capital structure determinants of listed firms in Pakistan using data for 2006-2011. Findings – We have found that bank-affiliated firms financing decisions are significantly different from that of non-bank affiliated firms with a common factor of the internal capital market. Bank-affiliated firm capital structure determinants of growth, asset tangibility, non-debt tax shield and operating risk show significantly different association with choice of leverage compared to non-bank affiliated firms. Policy implications – Our results show that group affiliated firms particularly bank-affiliated firms are the reason for market imperfections and have successfully eliminated the market distortions keeping others at a disadvantage. Hence, Policymakers are suggested to improve the regulatory system and its implementation. Originality/value – According to best of our knowledge, this is the first study to extend the literature of firm financing decisions in relation to bank-group affiliation in Pakistan.